ANALISIS PROSES PEMBELAJARAN MATEMATIKA BERBASIS DARING MENGGUNAKAN APLIKASI GOOGLE CLASSROOM PADA MASA PANDEMI COVID-19 DI KELAS VIII ABU BAKAR SMP IT AL FAHMI PALU: Analysis Of The Online-Based Mathematics Learning Process Using The Google Classroom Aplication Durinf The Covid-19 Pandemic In Class VIII Abu Bakar SMP IT AL Fahmi Palu - Qomaria, Esti; Hasbi, Muh.; Pathuddin (Universitas Tadulako, 2024)
This research is a qualitative descriptive study aimed at: obtaining a description of the analysis of the online-based mathematics learning process using the Google Classroom application during the Covid-19 pandemic in class VIII Abu Bakar SMPIT Al Fahmi Palu. The data collection techniques used questionnaires, documentation and interviews. The subjects in this study were all class VIII students of Abu Bakar SMPIT Al Fahmi Palu who were registered in the 2019/2020 school year. The number of students is 15 people. The results showed that the Google Classroom application can help and make it easier for teachers and students to carry out distance learning, especially in submitting materials and assignments. Based on the results of the study, it can be concluded that online-based learning using the Google Classroom application has been proven to be effective during the SFH (Study from Home) period due to the Covid-19 pandemic.